Safety management among contractor g7 in the construction of high rise building / Zulaikha Ismail - Ismail, Zulaikha (Faculty of Architecture, Planning and Surveying, 2013)
Construction is noisy, duty, hazardous and sometimes the most uninhabitable work place one can ever be exposed to. It is also an industry that contributes persistently to high accident rates especially fatalities. For example, employees are easily exposed to hazardous substances such as paints, thinners, glues, varnishes, asbestos, and also to toxic agents mainly from underground work. In order to ensure the safety workers construction sites are safe, the company construction must provide safety equipment and knowledge to employees them. Besides that, the company construction must provide the safety system and equipment which is should parallel with the standard of requirements and has a good implementation of safety management. This study has been developed with the aim to explore safety management standard that applied at the high rise building construction site and to examine safety management practice that applied at selected contractor g7 in construction site. This study also to identify suitable safety management for contractor in term of organization, application and training in the construction site and giving recommendation to improve safety management practice. The methodology for conducting the study involved literature review, data collection and analysis of results.The process of data collection involved obtaining primary data from the respondents by conducting questionnaire surveys at the selected construction of high rise buildings case studies, interview session with Safety Officer in construction site and from the site observation. From the study, it was found that generally, the safety management in the selected construction site is parallel with the standard requirements that provided by Authority and follow the regulations and act that comply in construction site.